Electrochemical Migratory Cyclization of N‐Acylsulfonamides. (15th June 2022) - Shi, Zhaojiang; Li, Yuanyuan; Li, Nan; Wang, Wei‐Zhen; Lu, Hao‐Kuan; Yan, Hong; Yuan, Yaofeng; Zhu, Jun; Ye, Ke‐Yin
Abstract: Benzoxathiazine dioxide, as a bioisostere of the clinically widely used diazoxide, exhibits interesting biological activity. However, limited success has been achieved in terms of its concise and direct synthesis. We report herein a facile electrochemical migratory cyclization of N ‐acylsulfonamides to access a diverse array of benzoxathiazine dioxides. The inclusion of electrochemistry is crucial for realizing such a novel transformation, which is substantiated both by the experiments and density‐functional‐theory calculations. Abstract : Electrochemical migratory cyclization of N ‐acylsulfonamides has been developed for the facile preparation of a diverse array of biologically interesting yet synthetically challenging benzoxathiazine dioxides.